Pengembangan Media Video Tutorial untuk Meningkatkan Keterampilan Menari Tari Kembang Manis pada Siswa Kelas 7 di SMP Santo Yoseph Jakarta Timur - Henriette, Pavita; Dwi Kusumawardani; Selly Oktarini (Program Studi Pendidikan Tari FBS UNJ, 2025)
This study aims to produce a video tutorial of the Kembang Manis dance for grade VII students of the Dance Arts subject. The study was conducted because the student learning outcomes with an average score of 65 were in the less good category. The results of the preliminary study showed that the causal factor was that the learning media used so far did not support achieving learning objectives. The methodology used was the ADDIE procedure research and development (R&D). Data collection techniques used interviews, observations, and questionnaires. The research targets were 19 grade VII students of the Dance Arts subject at SMP Santo Yoseph, East Jakarta. Numerical data were analyzed quantitatively and average data qualitatively. The results of the research and development at the review stage obtained an average score of 3.67 which means very good. The learning media expert gave an average score of 3.65 which means very good and the learning expert gave an average score of 3.87 which means very good with each category being very feasible. In the results of the field trial through the pretest, an average score of 67.1 was obtained and the posttest obtained an average score of 86.8, a percentage of 59.8% including the fairly effective category. In conclusion, video tutorial media is quite effective in improving the dancing skills of the Kembang Manis dance in grade VII students at SMP Santo Yoseph, East Jakarta.